Environmentally friendly technology for treatment of pesticide and ammonia contaminated water with electrochemical plasma - Nguyen Duc Hung,; Tran Van Cong,; Do Le Thanh Hung,; Tran Thi Ngoc Dung, (Vietnam Journal of Science and Technology, 2023)
Electrochemical plasma is formed by an electrochemical reaction with a high voltage direct current (DC) in a non-electrolyte solution such as distilled water to create a gaseous state on the electrodes. Under conditions of high voltage, strong electric field and suitable temperature rise due to the Joule-Lenz effect, an electrochemical plasma will appear and be noted by the glow on the electrode as well as the characteristic amperage of the reaction rate leading to a rapid increase in the electrochemical reaction. Plasma reactions produce substances with strong chemical reactivity such as H2, H2O2, or OH* free radicals, etc. in the aquatic environment. Electrochemical plasma formation can be controlled by technological parameters such as voltage, the distance between electrodes, conductivity, and the metallic nature of electrodes, etc.Using electrochemical plasma, it is possible to treat pollutants harmful to the aquatic environment such as 2,4-D; 2,4,5-T, and ammonia. In the process of treating polluted water by electrochemical plasma technology, chemicals and treatment materials are not used, so it is an environmentally friendly technology.